Efektivitas Konseling Kelompok Teknik Thought Stopping dalam Mengurangi Academic Burnout Siswa di SMP - Siti Aisyah Br Purba; Nasution, Fauziah (Institut Agama Islam Negeri Kerinci, Indonesia, 2025)
Academic burnout is a common issue among students, characterized by emotional exhaustion, depersonalization, and reduced personal accomplishment due to excessive academic pressure. This study aims to examine the effectiveness of group counseling services using the thought-stopping technique in reducing academic burnout among eighth-grade students at SMP Swasta PAB 3 Saentis. Using a quasi-experimental method with a pre-test post-test control group design, the study involved 20 students identified as having high to very high levels of academic burnout. Ten students were assigned to the experimental group, receiving group counseling with thought-stopping techniques, while the remaining ten in the control group received only informational services. Data were collected through a validated Likert-scale questionnaire and analyzed using descriptive and inferential statistics, including the Wilcoxon Signed-Rank Test and the Kolmogorov-Smirnov Two Independent Samples Test. The results showed a significant decrease in academic burnout scores in the experimental group (Wilcoxon Z = -2.805, p = 0.005), with most post-test scores falling into the low and moderate categories, while the control group remained in the moderate to high range. The difference between the two groups was also statistically significant (Kolmogorov-Smirnov Z = 1.789, p = 0.003). These findings indicate that group counseling using thought-stopping is effective in reducing academic burnout. The study suggests that incorporating the thought-stopping technique into school counseling programs can effectively enhance students' psychological well-being and reduce academic burnout. Practical implications include recommendations for school counselors to adopt thought-stopping as an intervention to address negative thought patterns contributing to burnout.